Competition between anisotropy and dipolar interaction in multicore nanoparticles: Monte Carlo simulation (2015)
Monte Carlo simulations combined with the Heisenberg model and Metropolis algorithm were used to study the equilibrium magnetic properties of magnetic multi-core nanoparticles of magnetite. Three effects were considered in this simulation: the Zeeman effect, magneto crystalline anisotropy, and dipolar interaction. Moreover, the influence of the size distribution (mean diameter and standard deviation) on the magnetization was analyzed. As an important result, a reduction of the equilibrium magnetization caused by the dipolar interaction and the magneto crystalline anisotropy was observed. On the other hand, the nanoparticle size increase produces an enhancement in the equilibrium magnetization, because of the lower influence of dipolar interaction. Cooling temperature effect was also observed, presenting a decrease in the equilibrium magnetization as the temperature was increased. The influence of the easy axis direction was studied.